Diagnosability problems of the exchanged hypercube and its generalization. Issue 2 (3rd April 2017) - Cheng, Eddie; Qiu, Ke; Shen, Zhizhang
ABSTRACT: We continue to study various properties of the generalized exchanged hypercube (GEH) structure. We also derive the g -good-neighbour diagnosability of the exchanged hypercube structure, a special case of GEH, i.e. the maximum number of faulty vertices that can be identified therein through self-diagnosis, where every non-faulty vertex has at least non-faulty neighbours, in terms of both the PMC and the comparison diagnostic ( ) models.